Addressing COVID-19 Spread: Development of Reliable Testing System for Mask Reuse - Haoxian Lu; Dawen Yao; Joanne Yip; Chi-Wai Kan; Hai Guo (Aerosol and Air Quality Research)
Abstract While the novel coronavirus pandemic (COVID-19) continues to wreak havoc globally, self-protection from possible infection by wearing a mask in daily life has become the norm in many places. The unprecedented demand for masks has now attracted attention on their filtration efficiency. Furthermore, the widespread use of disposable masks has led to shortage of filter materials and problems with their haphazard disposal. In this study, a testing system that is based on standardized methods has been established and enhanced to reliably measure the particle filtration efficiency (PFE) of masks. Quality control experiments that examine the filtration efficiency of polystyrene latex (PSL) particles that are 0.1 µm in size and sodium chloride (NaCl) particles that range from 0.01−1.0 µm are conducted to determine the reliability of the testing system. Moreover, various textile materials are tested to fabricate 3-layer face masks, and the PFE of these masks is tested by using the proposed testing system to find the most suitable materials and the likelihood of their reusability. Among the tested materials, polytetrafluoroethylene (PTFE) used as the membrane in the filter layer has the highest PFE of 88.33% ± 1.80%, which is mainly due to its dense and multilayer structure. The air permeability of the self-developed masks ranges from 1.41 ± 0.04 to 1.93 ± 0.08, less breathable than the commercial masks. The reusability of a mask that uses PTFE as the membrane in the filter layer is tested by gently washing the mask 30 times and then drying the mask in air before the PFE is measured. The PFE is only reduced by 10−20% after 30 washes, thus indicating the potential reusability of the mask. The findings in this study will contribute to reducing the pressure of mask shortages and are an environmentally friendly solution to the massive use of disposable masks.